2022
DOI: 10.1186/s13643-022-02150-9
|View full text |Cite
|
Sign up to set email alerts
|

Technology-based interventions for health challenges older women face amid COVID-19: a systematic review protocol

Abstract: Background Pandemics, such as COVID-19, are dangerous and socially disruptive. Though no one is immune to COVID-19, older persons often bear the brunt of its consequences. This is particularly true for older women, as they often face more pronounced health challenges relative to other segments in society, including complex care needs, insufficient care provisions, mental illness, neglect, and increased domestic abuse. To further compound the situation, because protective measures like lockdowns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Tackling misinformation is crucial to implementing mass vaccination, and in a study carried out with students in Germany, it was found that students who felt better informed about the scientific underpinning of government decisions and the vaccines, in general, were more likely to be vaccinated [ 35 ]. Methods based on social media and other technology can have value not only in countering misinformation but in addressing unmet needs as a result of the pandemic [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tackling misinformation is crucial to implementing mass vaccination, and in a study carried out with students in Germany, it was found that students who felt better informed about the scientific underpinning of government decisions and the vaccines, in general, were more likely to be vaccinated [ 35 ]. Methods based on social media and other technology can have value not only in countering misinformation but in addressing unmet needs as a result of the pandemic [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current COVID-19 pandemic has caused major problems for businesses and labor markets (Ge et al, 2022). It has also hurt public health, especially the physical and mental health of students (Aqeel et al, 2022) and older people (Su et al, 2022), who often have more serious health problems than other segments of society. Consequently, the performance of the existing health care system needs to be evaluated so that the success or failure of past policies can be figured out, needs can be assessed, priorities can be set, and evidence-based policies for the future can be planned (Farzadfar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the performance of the existing health care system needs to be evaluated so that the success or failure of past policies can be figured out, needs can be assessed, priorities can be set, and evidence-based policies for the future can be planned (Farzadfar et al, 2022). The use of technology in healthcare has the potential to greatly improve medical treatment (Su et al, 2022). Following the disruptive nature of telemedicine technology, researchers are striving to make it feasible and sustained around the globe, and developing countries, like Bangladesh, are not beyond it.…”
Section: Discussionmentioning
confidence: 99%
“…Women in particular bore a significant burden of the economic impact and personal hardships (Goldin, 2022), and elderly women were more prone to encountering significant health difficulties. Among these difficulties are intricate care requirements, mental health disorders, and a heightened susceptibility to domestic violence (Su et al, 2022). Unfortunately, lockdown measures implemented to curb the spread of the virus further exacerbated these challenges by disrupting or discontinuing essential health services that elderly women rely on.…”
Section: Literature Reviewmentioning
confidence: 99%